Is it safe? The effect of narrative vs. non-narrative messages on story-related knowledge of medicated abortion - Watts, Judy; Hubner, Austin; Pei, Jun; Barros Coelho, Michaella (Frontiers in Communication, 2025)
IntroductionEntertainment television programming has increasingly featured abortion content in storylines. To date, few studies have examined whether and how narratives vs. non-narratives impact learning and retention of polarizing health information. This study aims to investigate the potential for media-based learning from exposure to narratives.MethodsWe conducted a between subjects (format: narrative vs. non-narrative) by within subjects 2 (time: immediate post-test vs. delayed post-test) on a college population sample (time 1: n = 220; time 2: n = 125). Additionally, we tested both closed- and open-ended measures of knowledge by using a true/false test and free recall measure to test participants’ memory of factual-based knowledge of medicated abortion.ResultsBoth the non-narrative and narrative were equally effective on knowledge recognition (true/false scores), but the non-narrative was more effective for knowledge recall (open-ended scores). Individuals who were counter-attitudinal toward abortion exhibited greater knowledge recognition of medicated abortion at time 2 from watching the narrative. Knowledge recognition appeared stable at wave 2 while knowledge recall decayed at wave 2.DiscussionIndividuals are more likely to remember general safety and efficacy of medicated abortion regardless of format, but less likely to remember precise information about the medication from entertainment narratives. Narrative persuasion mechanisms were not found to mediate narrative exposure on knowledge about medicated abortion. However, narratives appear to facilitate learning about polarizing health information for those with unfavorable attitudes toward the topic.